Atmospheric Dispersion Study of TRS Compounds Emitted from a Pulp Mill Plant in Coastal Regions of the Uruguay River, South America - Orcellet, Emiliana Elizabeth (2016)
The atmospheric dispersion of total reduced sulfur (TRS) emissions from the pulp mill plant of Fray Bentos, Uruguay is simulated. The local authorities of the Environmental Monitoring Program (EMP) of Gualeguaychú, Argentina, received social complaints of malodor presence in different places of the region. An atmospheric dispersion model coupled to a boundary layer forecast model is used to simulate 11 events in which the EMP officials attended the scene in order to verify the situation. The validation of modeled winds with the observations from a meteorological tower indicates reasonably accurate wind forecasts. The spatial layout of the modeled TRS plumes is compared with the geographical distribution of points in the area where the social complaints were recorded. Nine of the 11 studied events are successful modeling cases since a positive (negative) in situ verification matches with a plume position over (far from) the site. In one of the two unsuccessful modeling cases, although the plume is marginally distant from the site, the average wind direction error is the largest one of all the events. In the other case the modeled plume is in fact over the site, but the situation was negatively verified. The reason for the disagreement could be the wind direction changes during the event. This was the longest modeled case that lasted for 7 hours and the plume was meandering during that time; first from SSW to the S, then back the SSW, and finally to the S and SSE. The conclusion of the study is that, despite the inherent uncertainty of numerical simulations, the implemented modeling system shows versatility and proves to be a useful tool not only for diagnostic studies but also for preventing conflictive situations since it can produce reasonably accurate forecast of plume position and its potential impact.